2020
DOI: 10.3389/fmicb.2019.02971
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhiza Changes the Impact of Potato Virus Y on Growth and Stress Tolerance of Solanum tuberosum L. in vitro

Abstract: Under the field conditions crop plants interact with diverse microorganisms. These include beneficial (symbiotic) and phytopathogenic microorganisms, which jointly affect growth and productivity of the plants. In last decades, production of potato (Solanum tuberosum L.) suffers from increased incidence of potato virus Y (PVY), which is one of most important potato pests. Arbuscular mycorrhizal fungi (AMF) are common symbionts of potato, however the impact of mycorrhizal symbiosis on the progression of PVY-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
1
23
2
Order By: Relevance
“…However, the use of similar methods to prevent chestnut blight in the Americas has never achieved the same effect (Liu et al, 2015;Andika et al, 2017;Abdoulaye et al, 2019). This is because the vegetative incompatibility groups of American chestnut blight are more complicated than those in Europe, which hinders the control effect (Wei et al, 2019;Dejasikora et al, 2020). Some phytopathogenic fungi that carry a certain type of virus can exhibit low pathogenicity (virulence decay) characteristics that are mediated by the virus, thereby protecting the host plant (Ding et al, 2019;Thapa and Roossinck, 2019).…”
Section: Fungal Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of similar methods to prevent chestnut blight in the Americas has never achieved the same effect (Liu et al, 2015;Andika et al, 2017;Abdoulaye et al, 2019). This is because the vegetative incompatibility groups of American chestnut blight are more complicated than those in Europe, which hinders the control effect (Wei et al, 2019;Dejasikora et al, 2020). Some phytopathogenic fungi that carry a certain type of virus can exhibit low pathogenicity (virulence decay) characteristics that are mediated by the virus, thereby protecting the host plant (Ding et al, 2019;Thapa and Roossinck, 2019).…”
Section: Fungal Virusesmentioning
confidence: 99%
“…During the infection process of pathogenic fungi, natural factors such as wind, rain, and the frequency of contact between insects and fungi are important factors that affect the pathogenesis of the host. Carneiro et al (2008) found that four out of 24 B. bassiana strains isolated from Brazil could kill 100% of 2-year-old S. frugiperda larvae; the mortality rate of S. frugiperda was as high as 100% on the seventh day after inoculation of the third instar larvae of S. (Hamel et al, 2012;Pereira et al, 2014;Clancy et al, 2017;Garrigues et al, 2018;Filizola et al, 2019;Kaur et al, 2019;Moisan et al, 2019;Toju and Tanaka, 2019;Ying and Feng, 2019;Dejasikora et al, 2020). frugiperda with the Metarhizium rileyi strain ZYSP190701 at a concentration of 1 × 10 8 conidia/mL.…”
Section: Spodoptera Frugiperda Biological Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were made by Larkin (2008) when a mix of AM fungi resulted in reduced stem canker and black scurf in the potato crop. AM fungi also act by alleviating H 2 O 2 in PVY stressed potato plants (Deja-Sikora et al, 2020). They can upregulate defense mechanisms upon herbivore attack against disease vectors such as aphids (Rizzo et al, 2020), as in the case with PVY.…”
Section: Tolerance To Plant Pathogens and Diseasesmentioning
confidence: 99%
“…Previous studies have shown that plant tolerance to stress, such as drought, salinity and high temperature, is closely related to the colonization of endophytic fungi [15,16]. Hence, the resource excavation of these associated endophytic fungi containing dark septate endophytes (DSE) is vital for improving the health and productivity of plants, especially for plant growth and vegetation restoration in degraded soils [17,18]. DSE represent a diverse group of endophytic fungi mainly involving ascomycetes, which propagate via conidia or asexual reproduction.…”
Section: Introductionmentioning
confidence: 99%